Fischer-Tropsch synthesis over Pd promoted cobalt based mesoporous supported catalyst - Gupta P.K.; Mahato A.; Gupta G.K.; Sahu G.; Maity S. (My University, 2025)
The catalytic conversion of syngas (CO + H2) through Fischer–Tropsch (FT) route using two identically prepared 0.1 wt.% palladium promoted mesoporous alumina (MA) and SBA–15 supported Co (15 wt.%) catalysts was investigated. The Fischer–Tropsch activity was carried out in a fixed bed tubular reactor at temperature 220°C and pressure 30 bar with H2/CO ratio ~ 2 having Gas Hourly Space Velocity of 500/hr. Detail characterizations of the catalysts were performed using different analytical techniques. The results showed that the SBA–15 supported catalyst displayed higher C6 –C12 selectivity (57.5%), and MA supported catalyst facilitated the formation of higher hydrocarbons (C13–C20) having 46.7% selectivity The use of both the support materials led to the production of liquid hydrocarbons through FT synthesis.